Math, asked by djharna770, 4 months ago

(5x - 3y)³
plsss answee​

Answers

Answered by rottasaritha
0

Step-by-step explanation:

(5x-3y)^3

this is in the form of

(a-b)^3b= a^3-3a^2b-3ab^2+b^3

=(5x)^3 - 3.(5x)^2.3y - 3.5x.(3y)^2 - (3y)^3

= 125x^3 - 3.25.x^2.3y - 3.5x.9y^2 - 27y^3

= 125x^3 - 225x^2 - 135y^2 - 27y^3

hope this helps you

Answered by yashasjain1
0

Answer:

(a - b)^{3}  = a {3}  - b^{3}   - 3ab7(a - b)

hence

(5x - 3y)^{3}  = 125 {x}^{3}  - 9 {y}^{3}  - 15x - 9y(5x - 3y)

(5x - 3y)^{3}  = 125 {x}^{3}  - 9 {y}^{3}  - 75x ^{2}  - 27y ^{2}

Similar questions